Comparison of structural design and future trends in composite hulls: A regulatory review - Zhiqiang Han; Jaewon Jang; Jean-Baptiste R.G. Souppez; Hyoung-Seock Seo; Daekyun Oh (International Journal of Naval Architecture and Ocean Engineering, 2023)
Recently, the International Organization for Standardization (ISO) standards associated with composite hull-structure design, including the method for estimating the mechanical properties of laminates necessary for design, have been revised. This study reviews the revisions concerning materials and analyzes the design trend of composite hull structures by comparing eight related rules, including classification society and domestic rules. The results reveal that the current design trend of hull laminates is to thoroughly consider the impact of several variables, including the weight fraction of reinforcement (glass content; Gc), fabric combination, and fabrication method, on the laminate properties. For illustration, these effects were verified with a typical glass-fiber-reinforced plastic vessel based on a case study, the experimental results of extant studies, and current standards. The industry design conditions, normal Gc (0.367) and high Gc (0.600), were selected and applied to two fabric combinations: chopped strand mat and chopped strand–woven roving. The hull laminate design results based on the revised ISO standards (ISO 12215) satisfied the safety and weight requirements for normal Gc in both cases. This may be attributed to the high mechanical properties suggested in the current standards regardless of how they reflect the effects of changes in fabric type, combination, and method on the mechanical properties of the laminates. For high Gc, the combination material case satisfied the safety requirements to a greater extent. and this can also be made lightweight. In contrast, the single material case based on the revised ISO standard may result in safety issues, mainly because the revised ISO standard reflects the adverse effects of design variables such as Gc and fabric blends on the laminate fabrication quality. Further, non-ISO rules should be revised in the future to reflect the effects of each variable in the material design according to the research trends of composite materials.